3D printing-based soft auxetic structures using PDMS-Ecoflex Hybrid. (13th March 2023) - Kim, Chae-Hwan; Kim, Hyun-Young; Kim, Jun-Ho; Kim, Jaehwan
Abstract: Auxetic structures with negative Poisson's ratio have received much attention due to their attractive behavioral properties in next-generation metamaterials and robotic applications. However, until now, there has been a lack of research into using soft materials to reliably develop a largely-deformable auxetic structures. Here, we develop soft polydimethylsiloxane (PDMS)-Ecoflex auxetic structures using a 3D printing technique, leading to high fabrication reliability and repeatability. Water-soluble filaments are employed to design sacrificial mold structures that quickly dissolve in warm water. By measuring the mechanical properties and light transmittance of soft composite membranes with various mixing ratios of PDMS and Ecoflex, the intrinsic characteristics of the composite membranes are determined. The newly fabricated soft auxetic structures composed of PDMS and Ecoflex composites always exhibit negative Poisson's ratio during stretching. The negative Poisson's ratio of the structure is maximized when PDMS and Ecoflex have a 2:1 mixing ratio and nominal strain is less than 5%. Advances in technology to reliably fabricate soft auxetic structures using 3D printers are believed to promote next-generation applications such as wearable sensors and energy-absorbing structures.